HISTORY OF GESTATIONAL DIABETES MELLITUS - Božić, Dragana; Dugalić, Stefan; Macura, Maja; Milinčić, Miloš; Novaković, Ivana; Gojnić, Miroslava (Medical Research, 2023)
The goal of this paper is to present the chronological development of knowledge about diabetes mellitus from the time of Hippocrates, through Langerhans and White, then how it was discovered that inadequate pancreatic function is the cause of diabetes mellitus, and that the kidney is only an organ that weakens due to unregulated pancreatic function. Studying gestational diabetes mellitus leads to better control of diabetes in pregnancy, better perinatal outcome with fewer peripartal and perinatal complications. In the second part of the paper, there is a review of the literature available on the Web of Science, in terms of the number of papers published over the years, in which areas and in which countries.